Inflammatory Bowel Disease-Associated Colorectal Cancer Epidemiology and Outcomes: An English Population-Based Study. (12th November 2022) - Birch, Rebecca J.; Burr, Nicholas; Subramanian, Venkataraman; Tiernan, Jim P.; Hull, Mark A.; Finan, Paul; Rose, Azmina; Rutter, Matthew; Valori, Roland; Downing, Amy; Morris, Eva J.A.
Abstract : INTRODUCTION: Patients with inflammatory bowel diseases (IBDs) of the colon are at an increased risk of colorectal cancer (CRC). This study investigates the epidemiology of IBD-CRC and its outcomes. METHODS: Using population data from the English National Health Service held in the CRC data repository, all CRCs with and without prior diagnosis of IBD (Crohn's, ulcerative colitis, IBD unclassified, and IBD with cholangitis) between 2005 and 2018 were identified. Descriptive analyses and logistic regression models were used to compare the characteristics of the 2 groups and their outcomes up to 2 years. RESULTS: Three hundred ninety thousand six hundred fourteen patients diagnosed with CRC were included, of whom 5, 141 (1.3%) also had a previous diagnosis of IBD. IBD-CRC cases were younger (median age at CRC diagnosis [interquartile range] 66 [54–76] vs 72 [63–79] years [ P < 0.01]), more likely to be diagnosed with CRC as an emergency (25.1% vs 16.7% [ P < 0.01]), and more likely to have a right-sided colonic tumor (37.4% vs 31.5% [ P < 0.01]). Total colectomy was performed in 36.3% of those with IBD (15.4% of Crohn's, 44.1% of ulcerative colitis, 44.5% of IBD unclassified, and 67.7% of IBD with cholangitis). Synchronous (3.2% vs 1.6% P < 0.01) and metachronous tumors (1.7% vs 0.9% P < 0.01) occurred twice as frequently in patients with IBD compared with those without IBD. Stage-specific survival up to 2 years was worse for IBD-associated cancers. DISCUSSION: IBD-associated CRCs occur in younger patients and have worse outcomes than sporadic CRCs. There is an urgent need to find reasons for these differences to inform screening, surveillance, and treatment strategies for CRC and its precursors in this high-risk group. Abstract :